STUDI LITERATUR : PENGUATAN KONSEP DAN PENERAPAN KURIKULUM MERDEKA BERBASIS DEEP LEARNING - Nurhaswinda; Nurfadilah; Annisa Bilbina Rachman; Febi; Azura Naysila Sahri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the conceptual framework and application of the deep learning approach in the implementation of the Merdeka Curriculum ineducation. The study employs a qualitative approach using a literature review method through descriptive analysis of 10 relevant scientific journals published between 2024 and 2026.The findings indicate that the deep learning approach has a strong connection with the principles of the Merdeka Curriculum because it emphasizes meaningful, reflective, contextual, and learner-centered learning. The application of this approach enhances conceptual understanding, critical thinking skills creativity, collaboration, and students’ active engagement in the learning process. Additionally, the implementation of deep learning also impacts the improvement of teachers’ pedagogical competencies through differentiated instruction, authentic assessment, and the integration of digital technology. Nevertheless, there are still various challenges, such as limitations in teachers’ conceptual understanding, learning support resources, and the need for continuous training. Therefore, comprehensive support from the education system and strengthening of teachers’ capacities are required so that the implementation of the Merdeka Curriculum based on deep learning can proceed optimally and sustainably in realizing 21st-century learning.